Case Report: Rapid response to gemtuzumab-ozogamicin in a pediatric patient with refractory systemic mastocytosis with AML1::ETO+ acute myeloid leukemia - Xue, Song; Chen, Man; Sun, Hui-Peng; Wang, Tong; Zhang, Li-Na; Cao, Xing-Yu (Frontiers in Immunology, 2025)
This article describes a 6-year-old patient diagnosed with “systemic mastocytosis with AML1::ETO+ AML”, he experience refractory disease during the course of treatment and salvage treatment was ineffective. The patient was administered gemtuzumab-ozogamicin therapy, resulting in rapid remission.